Analisis Pengarsipan Voucher Kas Keluar-Masuk Dan Perspektif Islam Terhadap Prakteknya Pada Pt. Winner Nusantara Jaya Tbk - Firdaus Firdaus; Monika Lintang Prastiwi (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2024)
PT Winner Nusantara Jaya Tbk. is the parent company of Winner Group, a leading property developer in Indonesia with more than 14 years of experience. Winner Group is known as an innovator and initiator of trends in the property industry in Batam City. The aim of this research is to analyze the filing of outgoing and incoming cash vouchers for PT Winner Nusantara Jaya Tbk, Batam City. This research uses a qualitative descriptive approach, namely presenting the results of the analysis found regarding the filing of outgoing and incoming cash vouchers for PT Winner Nusantara Jaya Tbk, Batam City. Data collection was obtained from interviews, observations and documentation of respondents and data sources analyzed. The results of the analysis show that the outgoing and incoming cash voucher activities of PT Winner Nusantara Jaya Tbk Batam City consist of Creating Incoming and Outgoing Cash Vouchers for PT Winner Nusantara Jaya Tbk, Printing Outgoing and Incoming Cash Vouchers from PT Winner Nusantara Jaya Tbk, Combining incoming and outgoing cash vouchers with receipts (purchase invoices, tax invoices, checks, proof of purchase and bank statements), filing vouchers into folders so as to minimize the error rate in preparing vouchers.